Heme Oxygenase-1 Signaling and Redox Homeostasis in Physiopathological Conditions - Valeria Consoli; Valeria Sorrenti; Salvo Grosso; Luca Vanella (Biomolecules, 2021)
Heme-oxygenase is the enzyme responsible for degradation of endogenous iron protoporphyirin heme; it catalyzes the reaction’s rate-limiting step, resulting in the release of carbon monoxide (CO), ferrous ions, and biliverdin (BV), which is successively reduced in bilirubin (BR) by biliverdin reductase. Several studies have drawn attention to the controversial role of HO-1, the enzyme inducible isoform, pointing out its implications in cancer and other diseases development, but also underlining the importance of its antioxidant activity. The contribution of HO-1 in redox homeostasis leads to a relevant decrease in cells oxidative damage, which can be reconducted to its cytoprotective effects explicated alongside other endogenous mechanisms involving genes like TIGAR (TP53-induced glycolysis and apoptosis regulator), but also to the therapeutic functions of heme main transformation products, especially carbon monoxide (CO), which has been shown to be effective on GSH levels implementation sustaining body’s antioxidant response to oxidative stress. The aim of this review was to collect most of the knowledge on HO-1 from literature, analyzing different perspectives to try and put forward a hypothesis on revealing yet unknown HO-1-involved pathways that could be useful to promote development of new therapeutical strategies, and lay the foundation for further investigation to fully understand this important antioxidant system.